Soil amendment mitigates mortality from drought and heat waves in dryland tree juveniles - Field, Jason P.; Law, Darin J.; Myers, Orrin B.; Barnes, Mallory L.; Breshears, David D.; Acuña, Kierstin M.; Feng, Xiao; Fontaine, Joseph B.; Ruthrof, Katinka X.; Villegas, Juan Camilo (Frontiers in Forests and Global Change, 2024)
Mortality of tree species around the globe is increasingly driven by hotter drought and heat waves. Tree juveniles are at risk, as well as adults, and this will have a negative effect on forest dynamics and structure under climate change. Novel management options are urgently needed to reduce this mortality and positively affect forest dynamics and structure. Potential droughtameliorating soil amendments such as nanochitosana biopolymer upcycled from byproducts of the seafood industry -may provide an additional set of useful tools for reducing juvenile mortality during hotter droughts. Nanochitosan promotes water and nutrient absorption in plants but has not been tested in the context of drought and heat stress. We evaluated factors affecting mortality risk and rate for dryland Pinus edulis juveniles (2-3 years old) in a growth chamber using a factorial experiment that included ambient and +4 o C warmer base temperatures, with and without a 10 day +8 o C heat wave, and with and without a nanochitosan soil amendment. The nanochitosan treatment reduced the relative risk of mortality, emphasizing a protective function of this soil amendment, reducing the relative risk of mortality by 37%. Importantly, the protective effects of nanochitosan soil amendment in delaying tree mortality under hotter drought and heat waves provides a new, potentially positive management treatment for tree juveniles trying to survive in the climate of the Anthropocene.